Neurotransmitter power plays: the synaptic communication nexus shaping brain cancer - Jayanta Mondal; Jason T. Huse (Acta Neuropathologica Communications)
Abstract Gliomas and brain metastases are notorious for their dismal prognosis and low survival rates, a challenge exacerbated by our incomplete grasp of the complex dynamics that govern brain cancers. Recently, a groundbreaking paradigm shift has emerged, highlighting the crucial role of synaptic communication between neurons and brain tumor cells in reshaping neuronal signaling to favor tumor growth. This review delves into the pivotal interplay of synaptic mechanisms, focusing on excitatory glutamatergic and inhibitory GABAergic pathways. Glutamatergic synapses utilize glutamate to propagate excitatory signals, while GABAergic synapses employ gamma-aminobutyric acid (GABA) to inhibit neuronal firing. Glutamatergic signaling can be broadly classified into ionotropic (NMDAR, AMPAR and kainite receptors) and metabotropic subtypes. The harmonious orchestration of these synaptic types is essential for normal brain function, and their dysregulation is implicated in neurodegenerative disorders such as Alzheimer’s disease and epilepsy. Emerging evidence reveals that glioma and brain metastatic cells exploit these synaptic pathways and neurotransmitters to enhance their proliferation and survival. In this review, we will first explore the intricate mechanisms underlying glutamatergic and GABAergic signaling. Next, we will summarize recent advancements in understanding how brain cancer cells hijack these pathways to their advantage. Finally, we will propose novel therapeutic strategies aimed at disrupting the aberrant neuron-tumor synaptic communication, offering potential treatment strategies for combating these otherwise incurable brain cancers.